Web-Based Application For Parenting Patterns In Vocational Schools In The Environment Of Politeknik Pelayaran Sorong - Muh Idris; Dodik Widarbowo; Yuniar Ayu Hafita; Yudha Herlambang P; Sappewali Sappewali (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Digitalization of education is a logical consequence of developments over time, a response to educational services that are experiencing changes in both the learning system and learning culture. Developments in the field of education are closely related to the term innovation. Innovation in the realm of education is an obligation for all educational actors. Moreover, the development of science and technology is growing rapidly. The parenting pattern that has been implemented in most vocational schools within the Ministry of Transportation is still more of a manual system that cannot be connected directly to digitalization. The aim of the process of developing digitalization of parenting patterns is expected to increase efficiency and optimization in many ways, including efficiency and optimization of parenting activities, connectivity between institutions or units involved in parenting, access to data related to parenting patterns, personal data of cadets and caregivers, as well as ease of use. information in accessing rules relating to parenting patterns. The research method used is a mixed type of research. Mixed research is the use of two types of research, namely qualitative and quantitative in one study. The research location is planned to be carried out at a vocational school under the Ministry of Transportation (Poltekpel Sorong). This research then produced an online-based digitalization development desktop software and was then named the see cadet application website. This development and research uses the ADDIE Development Model, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage.